Design de interfaces e usabilidade: proposta conceitual de um ambiente virtual de aprendizagem para o Centro de Educação a Distância da UFAM - Silva, Isabelle Colares da (Brasil, 2025)
The study aims to develop a digital interface for the UFAM Distance Education Center (CED/UFAM), using Learning Management System (LMS, called Moodle). The aim is to ensure that the LMS is intuitive and accessible, promoting an effective, efficient and satisfactory learning experience for all users (Nielsen, 2012). Using the Investigation Based on Design (IBD) methodology, this study sought to understand the context of distance learning at CED/UFAM and how the current usability of the platform impacts on the user experience. These users are considered active research objects for constant improvements in the development process. Development involves analyzing the situation and defining the problem, with the participation of users, identifying recommendations based on principles of psychology applied to design, and validating the proposed solutions. The results of this study can contribute to the compilation of good usability practices in the development of LMS's.